First record of experimentally induced salmon gill poxvirus disease (SGPVD) in Atlantic salmon (Salmo salar L.) - Thoen, Even; Tartor, Haitham; Amundsen, Marit; Dale, Ole Bendik; Sveinsson, Karoline Overn; Rønning, Hans Petter; Grønneberg, Estelle; Dahle, Maria; Gjessing, Mona Cecilie (Veterinary Research, 2020)
Salmon gill poxvirus (SGPV) infection is a common denominator in many cases of complex gill disease in the Norwegian salmon farming industry and may, as a single agent infection, result in salmon poxvirus disease (SGPVD). Experiences from the field suggest that stress may be a decisive factor for the induction of SGPVD. Here we investigated the effect of stress hormone treatment on SGPV kinetics and disease development. In our experiment, Atlantic salmon were divided into four groups. Two groups of fish received an intraperitoneal injection of hydrocortisone dissolved in a fatty vehicle, whereas fish in the other two groups received a sham injection of the vehicle. After 24 h, one group with hydrocortisone injection and one with sham injection were exposed to dead SGPV-infected fish. Plasma cortisol level, virus kinetics, virus localization, and pathological gill were monitored for 4 weeks post-exposure. Hydrocortisone injected fish displayed higher plasma cortisol and SGPV loads than non-hydrocortisone treated fish. Signs of SGPVD and ensuing mortality appeared only in fish exposed to the virus and injected with hydrocortisone around 2 weeks post-exposure. No clinical signs of disease or mortality were recorded in the other groups. Further, gill histopathology in diseased fish correlated well with SGPV load, with the infection apparently confined to gill epithelial cells. The current findings suggest elevated plasma cortisol being a prerequisite for the development of SGPVD and recommend minimization of stressful farming activities, particularly if SGPV infection has been previously identified.